The post-Olympic Games experience: A qualitative investigation of Australian Rio Olympians - Bennie, A.; Walton, C. C.; O`Connor, D.; Fitzsimons, L.; Hammond, T. (Western Sydney University, 2020)
Background: While research into Olympic Athletes` career transitions and retirement has led to a deeper understanding of important factors for athletes in this context, considerably less is known about the experiences of athletes in the immediate phase following an Olympic Games. Objectives: The purpose of this research was to investigate Australian Olympic athletes` experiences during the period of time immediately following the conclusion of the 2016 Rio Olympic Games. This involved investigating specific factors that influenced athletes` post-games realities of success, failure, and return to everyday life. Design: Qualitative-inductive Methods: Eighteen Australian Rio Olympic Games athletes (Female N=9, Male N=9) from a variety of team and individual sports participated in semi-structured interviews that explored their post-Olympic Games experiences. Thematic analysis was used to inductively analyse the data. Results: In the period immediately following the Rio Olympic campaign, many athletes felt a sense of relief before coming to terms with a post-Olympic `come down`. While positive and negative transitions back to reality following the Rio Games were influenced by performance expectations, positive transitions generally occurred when athletes had made plans for the post-Games phase and received strong support from family, teammates, and sport governing bodies. Conversely, negative experiences tended to occur where funding ceased, coach-athlete relationships fell apart, or team structures were dissolved following the Olympic event. Conclusions: Overall, athletes had a variety of experiences during the post-Olympic period and as such, it is critical to consider their needs individually. The findings of this project have implications at the micro (athlete, coach) and macro (National Sport Organisation) levels that could be used to better inform the targeted development of post-Olympic programs.